Epidemiology of Rhodococcus equi Strains on Thoroughbred Horse Farms - Morton, Anna C. (American Society for Microbiology, 2001)
Pulsed-field gel electrophoresis of restriction endonuclease-digested genomic DNA from a large collection of clinical isolates of Rhodococcus equi, an important pathogen of foals, was used to compare strain distribution between farms and over time. Forty-four strains were found among 209 isolates, with 5 of these accounting for over half the isolates and the 22 strains isolated more than once accounting for 90% of the isolates. The average genotypic diversity on each farm and in each year was found to be less than the genotypic diversity of the isolates taken as a whole, with 5.2% of the total diversity being due to differences between farms and 5.5% to differences between years. A small number of strains on each farm were found to have caused at least half the clinical cases of disease, and these varied between farms and, to a lesser extent, years. Most strains were found on more than one farm, and some very similar restriction patterns were found among isolates from different continents, indicating that strains can be very widespread. Multiple strains were isolated in five of the six cases in which more than one isolate from a single foal was examined, indicating that disease may commonly be caused by simultaneous infection with multiple strains. It was concluded that there are a number of different strains of R. equi which carry the vapA gene, and these strains tend to be widespread, but individual farms tend to have particular strains associated with them.